منهج البحث في علم أصول الفقه نحو تحديد المصطلح: Research Methodology in the Science of Jurisprudence Towards Defining the Term - Hiba, Lamine; Abdul Rahman, Noor Naemah; Ramli, Rushdi (Jurnal Fiqh, 2023)
The study sought to define the term methodology of the principles of jurisprudence, which studies began to search in the topic with different terminology. The method used in the research was: the lexical study of the terms with the researcher’s analysis. The study concluded that the definition of the research methodology in the principles of jurisprudence means the scientific methods, rules and methods used in the study of the subjects of the principles of jurisprudence. The study also showed the difference between two meanings of the term “usul al-fiqh methodology”.